Nontransverse factorizing fields and entanglement in finite spin systems - Cerezo, M. (2015)
We determine the conditions for the existence of nontransverse factorizing magnetic fields in general spin arrays with anisotropic XYZ couplings of arbitrary range. It is first shown that a uniform, maximally aligned, completely separable eigenstate can exist just for fields hs parallel to a principal plane and forming four straight lines in the field space, with the alignment direction different from that of hs and determined by the anisotropy. Such a state always becomes a nondegenerate ground state for sufficiently strong (yet finite) fields along these lines, in both ferromagnetic and antiferromagnetic-type systems. In antiferromagnetic chains, this field coexists with the nontransverse factorizing field hs′ associated with a degenerate Néel-type separable ground state, which is shown to arise at a level crossing in a finite chain. It is also demonstrated for arbitrary spin that pairwise entanglement reaches full range in the vicinity of both hs and hs′, vanishing at hs but approaching small yet finite side limits at hs′, which are analytically determined. The behavior of the block entropy and entanglement spectrum in their vicinity is also analyzed.